L'innovazione per lo sviluppo locale: l'Università per il territorio - Alfiero, Ciampolini (Firenze University Press, 2006)
This book presents the proceedings of the conference held on 12 March 2004 at the "Il Momento" theatre in Empoli. The aim of the conference was to explore the significant aspects of the presence of the University of Florence in the Empoli-Valdelsa area, involving the Faculties of Agriculture, Architecture, Economics, Engineering, Medical Surgery and Mathematical, Physical and Natural Sciences. This presence is a response to the plan for a progressive consolidation of the University in the Florentine metropolitan vast area, in line with functional settlement logic and integrally connected with the specific economic and social demands of the territory.